PENGARUH PEMBERIAN INSENTIF TERHADAP KINERJA PADA DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET KABUPATEN ROKAN HULU - -, Yarlis (Jurnal Mahasiswa Prodi SI Manajemen, 2013)
This research intent “ To know how incentive influence to performance On on duty financial Management Income and Rokan´s Regency Asset Upstream ”. This research intent to know how incentive influence to is ardour job on DPPKA.Population in observational it is exhaustive clerk on DPPKA that total 225 person, Sample that is taken as much 69 person by use of formula Slovin utilizes kusioner researches with likert´s scale and dianalisis´s data with tech analisis simple linear regression.Base observational result, gotten that signifikan´s influential Incentive to clerk performance at DPPKA. With signifikansi´s zoom 0,000 smaller one of( <0,05) berarti insentif berpengaruh positif dan signifikan terhadap kinerja pegawai.This research still circumscribed just menfokuskan on incentive and performance, expected for research next gets to be done by repair and is suggested to add other independent variable.